A Natural History of Disease Framework for Improving the Prevention, Management, and Research on Post-viral Fatigue Syndrome and Other Forms of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - O'Boyle, Shennae; Nacul, Luis; Nacul, Flavio E.; Mudie, Kathleen; Kingdon, Caroline C.; Cliff, Jacqueline M.; Clark, Taane G.; Dockrell, Hazel M.; Lacerda, Eliana M. (Frontiers in Medicine, 2022)
We propose a framework for the treatment, rehabilitation, and research into Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) using a natural history of disease approach to outline the distinct disease stages, with an emphasis on cases following infection to provide insights into prevention. Moving away from the method of subtyping patients based on the various phenotypic presentations and instead reframing along the lines of disease progression could help with defining the distinct stages of disease, each of which would benefit from large prospective cohort studies to accurately describe the pathological mechanisms taking place therein. With a better understanding of these mechanisms, management and research can be tailored specifically for each disease stage. Pre-disease and early disease stages call for rehabilitation strategies that may decrease the risk of long-term morbidity, by focusing on avoidance of further insults, adequate rest to enable recovery, and pacing of activities. Later disease stages require a more holistic and tailored management approach, with treatment - as this becomes available - targeting the alleviation of symptoms and multi-systemic dysfunction. More stringent and standardised use of case definitions in research is critical to improve generalisability of results and to create the strong evidence-based policies for management that are currently lacking in ME/CFS.